A novel Alzheimer disease locus located near the gene encoding tau protein - Jun, Gyungah; Ibrahim-Verbaas, Carla A.; Vronskaya, Maria; Lambert, Jean-Charles; Chung, Jaeyoon; Naj, Adam C.; Kunkle, Brian W.; Wang, Li-San; Bis, Joshua C.; Bellenguez, Céline; Harold, Denise; Lunetta, Kathryn L.; et al. (Nature Publishing Group, 2015)
APOE ε4, the most significant genetic risk factor for Alzheimer disease (AD), may mask effects of other loci. We re-analyzed genome-wide association study (GWAS) data from the International Genomics of Alzheimer’s Project (IGAP) Consortium in APOE ε4+ (10,352 cases and 9,207 controls) and APOE ε4- (7,184 cases and 26,968 controls) subgroups as well as in the total sample testing for interaction between a SNP and APOE ε4 status. Suggestive associations (P<1x10-4) in stage 1 were evaluated in an independent sample (stage 2) containing 4,203 subjects (APOE ε4+: 1,250 cases and 536 controls; APOE ε4-: 718 cases and 1,699 controls). Among APOE ε4- subjects, novel genome-wide significant (GWS) association was observed with 17 SNPs (all between KANSL1 and LRRC37A on chromosome 17 near MAPT) in a meta-analysis of the stage 1 and stage 2 datasets (best SNP, rs2732703, P=5·8x10-9). Conditional analysis revealed that rs2732703 accounted for association signals in the entire 100 kilobase region that includes MAPT. Except for previously identified AD loci showing stronger association in APOE ε4+ subjects (CR1 and CLU) or APOE ε4- subjects (MS4A6A/MS4A4A/ MS4A6E), no other SNPs were significantly associated with AD in a specific APOE genotype subgroup. In addition, the finding in the stage 1 sample that AD risk is significansignificantly influenced by the interaction of APOE with rs1595014 in TMEM106B (P=1·6x10-7) is noteworthy because TMEM106B variants have previously been associated with risk of frontotemporal dementia. Expression quantitative trait locus analysis revealed that rs113986870, one of the GWS SNPs near rs2732703, is significantly associated with four KANSL1 probes that target transcription of the first translated exon and an untranslated exon in hippocampus (P<1.3x10-8), frontal cortex (P<1.3x10-9), and temporal cortex (P<1.2x10-11). Rs113986870 is also strongly associated with a MAPT probe that targets transcription of alternatively spliced exon 3 in frontal cortex (P=9.2x10-6) and temporal cortex (P=2.6x10-6). Our APOE-stratified GWAS is the first to show GWS association for AD with SNPs in the chromosome 17q21.31 region. Replication of this finding in independent samples is needed to verify that SNPs in this region have significantly stronger effects on AD risk in persons lacking APOE ε4 compared to persons carrying this allele, and if this is found to hold, further examination of this region and studies aimed at deciphering the mechanism(s) are warranted.